P14-S Latency of Mismatch Negativity as a predictor of outcome in critically patients with subarachnoid haemorrhage. Issue 7 (July 2019) - Martinelli, Ilaria; Marchi, Angela; Naim, Giulia; Pruvost, Estelle; Ramdani, Celine; Sharshar, Tarek; Gavaret, Martine
Abstract : Background: Multimodal neurophysiological markers support clinical assessments in individuals with disorders of consciousness (DoC). Few studies focused on subarachnoid haemorrhage (SAH) related coma. Furthermore, these patients often need sedation during the acute phase, making behavioral and neurophysiological monitoring challenging. We investigated which neurophysiological marker could better predict outcome in acute DoC related to SAH. Methods: We studied 14 SAH patients admitted in the Sainte Anne hospital neurological ICU, between Oct 2017 and June 2018. All patients underwent within the first 72 h: clinical evaluation, EEG and multimodal evoked potentials (somatosensory potentials, brainstem auditory evoked potentials (BAEPs), late latency event-related potentials, N100 and mismatch negativity (MMN)). Quantitative EEG analysis using spectral and connectivity analysis was performed. According to the Glascow Outcome scale (GOS), we defined two clinical outcome groups: favorable (F) and unfavorable (UF). Results: Clinical examination, EEG visual and quantitative analysis, presence of N20, BAEP, N100 and MMN were not significantly different in the two groups. However, mean latencies of N100 ( F = 80 ms; UF = 106 ms;) and of MMN ( F = 139 ms; UF = 197msec) were significantly different in the two groups (Mann Whitney test, respectively p = 0.017 and p = 0.035). Conclusions: This study suggests that during the acute phase, in sedated patients with DoC related to SAH, latencies of N100 and latencies of MMN could be more discriminatory than the "classical" interpretation of these markers (present/absent) and the EEG analysis, in term of prognosis. These results need to be confirmed in a larger study.